Ответ:
х=-100;х=-10
Пошаговое объяснение:
х-(-84,6)=-15,4
х+84,6=-15,4( - на - даёт +)
х= -15,4-84,6
х=-100
х-(-8 5/6) =-1 1/6
х+ 8 5/6= -1 1/6
х= -1 1/6 - 1 5/6
х=-10
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Ответ:
х=-100;х=-10
Пошаговое объяснение:
х-(-84,6)=-15,4
х+84,6=-15,4( - на - даёт +)
х= -15,4-84,6
х=-100
х-(-8 5/6) =-1 1/6
х+ 8 5/6= -1 1/6
х= -1 1/6 - 1 5/6
х=-10
x+84.6=-15.4
3. x(-8 5/6)=11/6
x(-53/6)=11/6
-53/6x=11/6
умножим обе части равенства на -6/53:
x=-11/53